(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of Compensation, Work Discipline and Motivation on Employee Productivity at the Department of Population and Civil Registration of Bantul.This research is included in quantitative research. The population in this study is 53 employees. The sampling technique used in this research is saturated sample. The data collection technique uses a questionnaire which is measured using a Likert scale. The data analysis technique used is multiple regression test with SPSS Version 25. The results of this study indicate that compensation affects employee productivity, this is evidenced by the results of the individual parameter significance test or the t-test where tcount is greater than ttable, namely 4.129 ˃ 2.00958. The results of the study of Work Discipline do not affect employee productivity, this is evidenced by the results of the individual parameter significance test or the t-test where tcount is smaller than ttable, namely -0.598 ˂ 2.00958. The results of the study Work motivation affects employee performance, this is evidenced by the results of the individual parameter significance test or t-test where tcount is greater than ttable, namely 3.222 ˃ 2.00958.